2008
DOI: 10.1177/0269881107082624
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of prolactin in rodents and humans: breast and prostate cancer

Abstract: Drugs and chemicals shown to induce mammary carcinogenesis in the rat/rodent via prolactin excess have traditionally been argued to pose little or no risk to humans in a regulatory toxicology context. The basis for this assumption is reviewed and placed into context with new evidence in humans that prolactin may be a tumour promoter in the breast and prostate. This evidence includes epidemiology, patient studies involving endocrine evaluation and molecular biology in human cells. It is concluded that hyperprol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 72 publications
(92 reference statements)
1
46
0
1
Order By: Relevance
“…This provides further evidence that some undefined factors, such as prolactin, may be relevant regarding the elevated incidence of breast cancer in schizophrenia. 13,19,24,25 This issue is discussed further in the next section.…”
Section: What Is the Incidence Of Cancer In Schizophrenia?mentioning
confidence: 99%
“…This provides further evidence that some undefined factors, such as prolactin, may be relevant regarding the elevated incidence of breast cancer in schizophrenia. 13,19,24,25 This issue is discussed further in the next section.…”
Section: What Is the Incidence Of Cancer In Schizophrenia?mentioning
confidence: 99%
“…risperidone and amisulpiride) also increase prolactin serum levels and this can lead to hormonal related side effect effects such as menstrual abnormalities, galactorrhoea and sexual dysfunction. In the long term high prolactin levels can lead to reduced bone mineral density (Haddad and Wieck 2004) and a potential increased risk of some cancers (Harvey et al 2008).…”
Section: Potential Risks Of Antipsychoticsmentioning
confidence: 99%
“…A recent meta-analysis that included fewer studies than our systematic review (Catts et al, 2008) reported a 12% increased risk (Standardised Incidence Ratio [SIR] 1.12, 95% CI 1.02-1.23) with a more recent UK study reporting an increased risk of 52% in schizophrenia adjusting for recognised confounders such as poverty (Hippisley-Cox et al, 2007). One can only speculate over the role of prolactin and mammary carcinogenesis, however in animal toxicity and molecular studies, it has been recognised over many years (Harvey 2008) that there is a very strong association. The US Nurses' Health Study evaluated prolactin samples from 32,826 patients with normal prolactin levels during the period 1989 to 1990 and these subjects have been extensively followed over 20 years, providing conclusive evidence linking prolactin and breast cancer in the general population.…”
Section: Possible Association With Cancermentioning
confidence: 99%
“…Screening rates for schizophrenia patients are very low compared with the general population for an illness that is very common (lifetime prevalence 1 in 9 and rising) and often curable . Hyperprolactinaemia has also been linked to pituitary adenomas and adenocarcinomas and putatively to prostate cancer (Harvey et al, 2008). The US Food and Drug Administration Adverse Event Reporting System pharmacovigilance database study strongly linked risperidone (adjusted reporting ratio 18.7) with the highest frequency of pituitary adenomas compared with haloperidol (5.6), ziprasidone (3.0) and olanzapine (2.3) (Szarfman et al, 2006).…”
Section: Possible Association With Cancermentioning
confidence: 99%